2014
DOI: 10.1080/15287394.2014.866923
|View full text |Cite
|
Sign up to set email alerts
|

Açaí (Euterpe oleraceaMart.): A Tropical Fruit with High Levels of Essential Minerals—Especially Manganese—and its Contribution as a Source of Natural Mineral Supplementation

Abstract: Açaí is a fruit from the Brazilian Amazon region, with an exotic flavor, possessing high antioxidant and anti-inflammatory properties. Based on these properties, the fruit is classified as one of the new "super fruits." The mean daily consumption of açai pulp may reach 300 ml in several Brazilian regions. Further, this fruit is also gaining popularity in Europe and North America. In this context, the aim of this study was to assess the levels of some essential minerals in freeze-dried açaí pulp obtained in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 48 publications
(44 reference statements)
0
8
0
1
Order By: Relevance
“…However this study confirms that populations from Northern Brazil have significantly higher Mn levels in comparison to people from other Brazilian states 16,22 . Açai fruit, a typical Amazon region berry, has high levels of essential elements, especially Mn 32 , and its consumption could be associated with high blood Mn levels. However, the interpretation of our findings with respect to such status is limited by the lack of information on individuals' diet (for example, nutrients quantification in food more consumed by our study population).…”
Section: ▄ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However this study confirms that populations from Northern Brazil have significantly higher Mn levels in comparison to people from other Brazilian states 16,22 . Açai fruit, a typical Amazon region berry, has high levels of essential elements, especially Mn 32 , and its consumption could be associated with high blood Mn levels. However, the interpretation of our findings with respect to such status is limited by the lack of information on individuals' diet (for example, nutrients quantification in food more consumed by our study population).…”
Section: ▄ Discussionmentioning
confidence: 99%
“…Thus, the information on food frequency consumed during the dry and rainy season in this study was based on a study of 2001 1 , which was performed in the community of Brasília Legal, nearby our study area. Another limitation is that we did not evaluate the nutrient contents of the main foods consumed in this region during the two study periods, while it is known that nutrient contents can be different among different places 17,32 . These limitations prevented us from identifying more specific exposure pathways to blood Cu, Mn, Se, Zn, carotenoids and vitamins in this population.…”
Section: ▄ Discussionmentioning
confidence: 99%
“…4% acai extract) was rather rich in Li (>100 µg Li/L). It has been previously reported that Acai pulp contains substantial concentrations of other trace elements, including iron, zinc, copper and manganese [36]. In addition to acai extract, Acai 28 black contains lemon juice concentrate, guarana and herb extracts, which possibly supply Li to this energy drink.…”
Section: Analysis Of Beveragesmentioning
confidence: 99%
“…Acai showed no toxicity in experimental models [31][32][33][34][35][36] nor any significant differences in the body weight or food consumption [17,31,32,36], suggesting potential applications in the prevention of various disease. Conversely, Mn, which is abundant in acai, suppresses Fe absorption, suggesting a risk for anemia [37]. The kidneys are prone to hypoxia because of their high energy consumption [38].…”
Section: Discussionmentioning
confidence: 99%